The realisation of goal-driven airport enclosures intrusion alarm system. (2017) - Yao, Xiaofeng
Airport enclosures intrusion alarm system is the first defence line in airport security, and has an important guarantee to maintain the safety of airport and passenger. The traditional signal-driven enclosures security system has many disadvantages, such as backward measures, high false alarm rate, non-comprehensive, difficult to maintain and easy to damage the cable network etc. Aiming at aforesaid actualities, a goal-driven airport enclosures intrusion alarm wireless sensing system based on ZigBee technology is presented in this paper. The false alarm and missed alarm rate of this system was very low, which meets the monitoring requirements throughout the day and brings a revolutionary technological innovation for the airport enclosures intrusion detection. It is worthy of popularisation and application in the security systems.